Polarization of contact forces in multi-contact systems - Dumont, Serge; Fortin, Jerôme; Ouafik, Youssef (European Journal of Computational Mechanics, 2010)
The aim of this study is to identify the homogenized laws modeling the overall behaviour of multi-contact systems. At the moment, these systems are generally analyzed either by continuum mechanics or micro-mechanics and a multi-scale approach. These approaches differ from the phenomenological approach traditionally used for modeling the behavior of solid materials which is based on mathematical formulations developed in the framework of thermodynamics, whose constants are determined from results of laboratory tests. The lack of basic physics in these formulations leads to mathematical models that are often complex and difficult to identify. The multi-scale approach appears well suited to address these difficulties. This study aims at quantification using the Discrete Element method (Jean, 1999; Fortin et al., 2005) polarization phenomena of contact forces.